Decoding the Life of Undergraduates through Signs of College Memes on Universitas Pershitpostingan Indonesia’s Facebook Fanpage - Sitompul, Yuniar; Rosita, Nur (English Language and Literature, 2024)
This research is aimed to describe the life of undergraduates through signs, the denotative and connotative meanings of college memes shared by Universitas Pershitpostingan Indonesia’s Facebook Fanpage. Using a qualitative approach and Barthes' semiotic theory (1967), this research analyzed 42 memes representing the life of undergraduates. The main findings encompassed the dominance of verbal signs, including textual narratives about various aspects of university life and challenges faced by undergraduates. Additionally, the analysis indicated that non-verbal signs, such as images and snippets from movies or cartoons, played a significant role in constructing rich visual narratives about student life. These college memes served not only as entertainment but also reflected the reality, challenges, and experiences of students in higher education. Denotatively, the memes conveyed messages about various academic aspects, while connotatively, college memes tended to exhibit a critical tone towards various aspects of campus life. In conclusion, this research provides a deep understanding of the meanings embedded in college memes, and comprehensively portrays the challenges, dynamics, and humorous aspects of the university experience, strengthening identification and solidarity among the student community.